(untitled) (Journal of Technology and Operations Management, 2017)
The purposes of this study were to explore the production marking situation and analyze the SWOT Analysis of production of the salted kulao fish manufactured at Tak Bai, Narathiwat province. The samples were three salted kulao fish producer. The data collection were used the questionnaires as in depth interview. The results were found that strength of salted kulao fish were famous, good quality and acceptable product from consumers. However, the products still in oligopoly market that had more negotiated power. Also, the producers could retained old consumers and expanded increased new consumers. The weakness in products was complicated process because it must have carefully steps. The selling strategy of the products was lowest because excessive demand. The opportunity of products was high requirement from consumers and still popular for souvenir. Threat of this product was low materials as fresh kulao fish because it seasonal fish.